A retrospective review on the utilisation of meropenem in a tertiary hospital setting - Mohun, Shameeda (University of the Witwatersrand, Johannesburg, 2024)
Introduction: The discovery of antibiotics is widely regarded as a groundbreaking accomplishment in the medical industry, as it has facilitated the elimination of countless diseases. Nonetheless, the overuse and reckless consumption of these medicines have led to a global upsurge in antibiotic resistance, particularly in broad-spectrum antibiotics such as meropenem, which are often prescribed for severe infections. Aim: The aim was, therefore, to assess the utilisation trends of meropenem in treating patients at a tertiary hospital located in the North-West Province of South Africa. Methodology: This study involved a retrospective review of hospital records at a 396-bed tertiary hospital in the public sector of South Africa, for patients who were prescribed meropenem between January and December 2021. A total of 218 patient files were included in the analysis after removing the duplicates and incomplete files. Variables investigated were patient demographics, prescribing criteria, diagnosis, treatment indication, microorganisms, and sensitivity cultures, as well as the appropriateness of prescribing. Descriptive statistics were employed to analyse the data. Results: Meropenem was primarily used empirically in adult patients (65.1%), while clinicians treating paediatric patients generally reserved its use for definitive cases (55.1%). Recording of the source of infection was poor with 72.1% of adults and 96.6% of paediatrics lacking such documentation. Although all prescriptions analysed were deemed valid, only a small percentage of treatments were considered appropriate (3.1% in adults). The study also revealed that clinicians frequently ordered microbiological cultures and blood sensitivity tests prior to administering antibiotics, at rates of 50.4% in adults and 71.9% in paediatrics. Notably, the most cultured bacteria were Klebsiella pneumoniae (25.2%) in paediatric patients and Acinetobacter species (25.0%) in adults. Conclusion: The study's results reveal a clear contrast between suggested protocols and clinical practices in the real world, stressing the pressing need for effective antimicrobial strategies to counter the growing threat of meropenem resistance. Several areas of concern were identified, including non-adherence to guidelines, insufficient step-down therapy, and incomplete documentation. Despite being a broad-spectrum antibiotic intended for definitive diagnoses, meropenem is often prescribed empirically, further highlighting the need for continuous medical education, practical therapeutic committees, and frequent drug utilisation evaluations to tackle this issue
A research report submitted in partial fulfillment of the requirements for the degree of Masters of Science in Medicine, Clinical Pharmacy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg 2024
Keywords: Meropenem; Antimicrobial resistance; Drug utilisation study; SDG-3: Good health and well-being